Peningkatkan Keberlangsungan Usaha UMKM KIKA Melalui Pelaporan Keuangan dan Pengelolaan Produk Sisa - Anna Sumaryati; Kusni Ingsih; Hayu Wikan Kinasih (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
UMKM KIKA as an Small Medium Enteprise which was formed at the initiative of one of the residents who saw potential in the community around Bulu Lor village, Semarang City. The business has been engaged in is in the form of food processing, such as traditional cakes, pastries and cakes. Through the pre-survey activities carried out, several problems were found that were of concern and needed to be provided with solutions. Solutions related to product innovation will be provided through training on making derivative products from the remaining products produced by UMKM KIKA. Thus, it will minimize the waste costs that arise from the product. Apart from that, training is also carried out related to the preparation of financial reports. The method of implementing activities is carried out in three stages, including surveys, implementation, and evaluation. Based on the evaluation results it is known that 80% of UMKM KIKA members are interested in preparing financial reports, and 100% are interested in managing leftover raw materials into new products.